Factors affecting entrepreneurial intention and entrepreneurial attitudes among rural Tunisian women - Maayoufi, Dorsaf; Péli, László; Áldorfainé Czabadai, Lilla (Acta Carolus Robertus, 2023)
Entrepreneurship is strongly affected by the intentions and attitude of an entrepreneur. Women entrepreneurs are the most important elements of success in all communities, but they are most often neglected by society which leads to a different attitude and intention of women towards entrepreneurship as compared to men. Both societal and familial factors are responsible for the development of the entrepreneurial attitude and intentions of an individual. Tunisian society is more rigid towards women’s entrepreneurship due to the presence of patriarchal nature which causes a lower interest of women in business activities. This review provides insight into the factors responsible for the attenuation of entrepreneurial attitude (EA) and entrepreneurial intentions (EI) among rural women of Tunisia. We reviewed previous literature for this cause and tried to identify the most prominent effects of societal, cultural and familial factors affecting the EA and EI of women residing in rural Tunisia. Results from the data yield some factors which had a direct or indirect influence on the EA and EI of rural Tunisian women which included social capital, family support (Husband and parents), entrepreneurial education, entrepreneurial training, regional context (Culture), self-efficacy, pull factor, an emotional factor, lack of managerial skills, risk-taking, role model (Parental and organizational) and reference groups.
Keywords: Tunisia; rural women; enterpreneurial intentions